MODERN APPROACH TO BREAST CANCER SCREENING - Feruza Sharofovna, Khalikova (European Journal of Life Safety and Stability (2660-9630), 2021)
International Agency for Research on Cancer and WHO Cancer Division, proven in 7 prospective studies, – mammography (film or, better, digital) in all (regardless of risk groups) women included in the "targeted" cohort of 50-69 years